2014
DOI: 10.2500/aap.2014.35.3768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atopic features between children and adults with eosinophilic esophagitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Thus, it is not unusual for EoE patients to suffer atopic exacerbations during the pollen season and to seek out allergist care because of it, thereby providing an increased likelihood of receiving a diagnosis of EoE during the same season. Atopic features and allergy sensitization patterns in EoE patients are similar to those of atopic non‐EoE individuals living in the same geographical area and exposed to common allergens , with no significant differences regarding family background of atopy, and personal history of allergic rhinitis, atopic dermatitis, immunoglobulin E‐mediated food allergy, or sensitization to aeroallergens between the two groups, either in children or in adults .…”
Section: Discussionmentioning
confidence: 70%
“…Thus, it is not unusual for EoE patients to suffer atopic exacerbations during the pollen season and to seek out allergist care because of it, thereby providing an increased likelihood of receiving a diagnosis of EoE during the same season. Atopic features and allergy sensitization patterns in EoE patients are similar to those of atopic non‐EoE individuals living in the same geographical area and exposed to common allergens , with no significant differences regarding family background of atopy, and personal history of allergic rhinitis, atopic dermatitis, immunoglobulin E‐mediated food allergy, or sensitization to aeroallergens between the two groups, either in children or in adults .…”
Section: Discussionmentioning
confidence: 70%
“…In addition to atopic disorders such as atopic dermatitis and asthma (19,20), EoE has been observed in the presence of other comorbidities, including a spectrum of inherited connective tissue disorders (CTD) characterized by hypermobility syndrome, suggesting common disease pathways (21). For instance, TGF-β-mediated fibrotic responses have been implicated in both esophageal remodeling and dysmotility in EoE and the CTDs Marfan syndrome and Loeys-Dietz syndrome (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been hypothesized that eosinophils migrate to the esophagus in response to various ingested and/or inhaled allergens, thus associating EoE to allergy‐induced diseases . As a result, high prevalence of atopic diseases (eg, asthma, allergic rhinitis [AR] and atopic dermatitis [AD]) and sensitization to food and environment allergens is seen in pediatric and adult EoE populations . However, most studies describe concomitant disease as self‐reported by the patients and thus are prone to bias and underrepresentation or overrepresentation of comorbidities…”
mentioning
confidence: 99%